Counselling for self-employment: the application of decision support system - Smaliukienė, Rasa; Bekešienė, Svajonė; Dudzevičiūtė, Gitana (Business: Theory and Practice, 2012)
The article considers the provision of decision support opportunities for unemployed people who are seeking for self-employment and opening a new business. The purpose of this paper is to consider the application of decision support system (DSS) for e-counselling of the unemployed, specially focusing on self-employment solutions. The development of DSS is tackling main social challenges of the long-term unemployed: it conveys an experience from previous employment; provides new business opportunities, which are highly related to person’s hobbies; and it connects people by developing complementary groups of same interests and same positive attitudes towards entrepreneurship. From a technical perspective we suggest that it is advisable to place a workflow engine at the core of the Internet based e-decision making system. This will let us generate and manage personalized and adaptable individual recommendation access. The access flow algorithm of DSS consists of three interconnected blocs: the first bloc is constructed for the self- containment as process logic and analysis of consumer objectives; the second one analyses person’s ability for entrepreneurship, it also evaluates individual’s overall motivation to start his own business; and the third bloc provides with potential complementary business partners or business start-up.